The Development of Russian-Language Schools in Ukraine (Late 30s-40s of the XXth Century) - Svitlana Shevchenko (Pedagogical Discourse, 2013)
The given article considers organization of Russian schools in teaching children in  Ukraine in the late 30ʼs and 40ʼs in the twentieth century on the base of archived documents It is considered that with beginning of collectivization   cultural life of national minorities fell into decay  except Russian; it is shown that the beginning of 30th was characterized by such phenomenon in the development and functioning of schools of national minorities, as  force Russification. It is traced, that Soviet Government tried to create common requirements as to   construction of educational process of schools on the whole territory of the USSR and to give  the peoples  who lived in Ukraine, real possibility to develop national culture and language. It is distinguished, that during realization of governmental politics as to formation of the Russian minorities of  special meaning acquired a problem in the system of formation Russian secondary schools, making lifeliving  and effective bodies from  guidance, organizational and scientifically-methodological providing. It is investigated, that the content of educational programs and plans of Russian schools fully meet the requirements  during the given period.